A 3D Mechanism-driven Hexagonal Metamaterial: Evaluation of Auxetic Behavior. (1st November 2021) - Su, Yutai; Xu, Xianchen; Shi, Jing; Huang, Guoliang
Highlights: A novel 3D sliding induced hexagonal auxetic (SIHA) metamaterial is proposed. The auxetic behavior of SIHA design is verified by using mechanics analysis, numerical analysis, and experiment. Compared with the re-entrant honeycomb structure, higher compression resistance and more stable auxetic behavior are observed. Friction condition is also found to significantly affect the properties of the SIHA structure. Abstract: This paper investigates an unconventional 3D printable auxetic metamaterial realized by a unique sliding mechanism. The concept of 3D sliding induced hexagonal auxetic (SIHA) metamaterial is proposed with stable auxetic behavior and improved compression load response, as compared with the conventional re-entrant structure. For a single SIHA lattice cell, the theoretical model concerning the sliding mechanism is developed and verified by both finite element analysis (FEA) and experiment. Furthermore, the compression properties of the periodic SIHA structure are evaluated by FEA with experimental verification. A 3D conventional re-entrant honeycomb (REH) structure is adopted for comparison. It is shown that the FEA results agree with the experimental results, and overall superior performance of SIHA structure is obtained, which is reflected by higher compression resistance and more stable auxetic behavior. Moreover, the sensitivity of performance with respect to the friction coefficient in the sliding mechanism is investigated. It is found that the performance and auxetic behavior of the SIHA metamaterial is sensitive to the friction condition. Force-strain curve increases with the input friction coefficient, while an excessive friction coefficient may cause undesirable effects on the slip mechanism. Overall, the friction sliding and collapsing structural mechanism-driven structures could provide a new way to entrap elastic energy under compression deformations. Graphical Abstract: Image, graphical abstract